Pengaruh Kualitas Pelayanan terhadap Loyalitas Pasien yang Dimediasi Oleh Pemasaran Relasional dan Kepuasan Pasien - Devis Pranata Indra; Yanuar Ramadhan; Endang Ruswanti (Jurnal Health Sains, 2022)
Progress in the economic field, indirectly has an impact on the rapid development in the field of health, especially hospitals. The best service is currently the main focus for each hospital to increase the competitiveness and selling power of the hospital. The study aims to analyze the effect of quality of service on patient loyalty at Kartika Pulomas Hospital East Jakarta, with patient satisfaction and relational marketing as intervening variables. The study was conducted by collecting quantitative data through the dissemination of questionnaires to 255 respondents. The analytical technique used is Structural Equation Modelling (SEM) with lisrel. The results showed that quality of service had a significant effect on patient loyalty with patient satisfaction and relational marketing as intervening variables; Quality of service has a significant effect on relational satisfaction and marketing, but has no effect on patient loyalty; Patient satisfaction and relational marketing have a significant effect on patient loyalty. Managerial implications based on the results of the study is that it is recommended that hospitals make information containers both printed and digital; evaluate the running of SPO (Standard Operating Procedure); Complete supporting inspection facilities; Improve employee abilities and skills through seminars or training